Predictors of Intention to Consume Genetically Modified Oil among Personnel of Community Health Care Centers in Yazd, Iran: An Application of the Theory of Planned Behavior - Masoumeh Abbasishavazi; Bahador Hajimohammadi; Zahra Hajebrahimi (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Genetically Modified (GM) food is a point of debate in the world. There have been few relevant studies in Iran, so this study aimed to predict the consumption of genetically modified oil by the staff of health centers based on the planned behavior theory. Methods: In this cross-sectional study, 105 staff members of health care centers of Yazd in Iran completed a researcher-made questionnaire in 2017. The questionnaire validity and reliability were verified. The data were analyzed via SPSS 11.5, by Pearson correlation coefficient and linear regression model. The data were analyzed using SPSS software and at the number below 0.05 regarded as significant. Results: Attitudes and subjective norms had the strongest positive, significant correlations with consuming genetically modified oil (r=0.619, r=0.526, p<0.01) respectively. Predictors of consuming intent for genetically modified oil showed that 43.2% of the variance of intention was determined by the attitude, subjective norms, and perceived behavioral control. Conclusion: Since the attitude was identified as the strongest predictor of consuming intention of genetically modified (GM) oil, studying the factors influencing the attitude toward GM food in different social levels of Iran is recommend. The results provide important evidence for supporting the use of this theory in predictions of food-related consumption behaviors, especially in the area of new food products